2015
DOI: 10.1002/2015ja021047
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and solar activity dependence of 1967–2005 thermospheric density trends derived from orbital drag

Abstract: We examine 1967–2005 thermospheric mass density trends (as well as 1967–2013 trends) derived from satellite orbit data, as a function of altitude, solar flux, and geomagnetic activity. At 400 km altitude, the estimated 1967–2005 trend is −2.0 ± 0.5% per decade. The estimated trends become increasingly negative with increasing height between 250 and 575 km, suggesting an exospheric temperature trend of −1 to −2 K per decade, which is much smaller than temperature trends that have been inferred from ground‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(177 citation statements)
references
References 30 publications
11
155
1
Order By: Relevance
“…This gives cooling rate of ∼(3-4) K/decade analyzing a period of 30-40 years. This is close to an exospheric temperature trend of À1 to À2 K/decade estimated from satellite drag observations (Emmert, 2015) and much smaller than Tex trends inferred from ground-based ISR measurements: À18 K/ decade for noontime exospheric temperature at Millstone Hill (Oliver et al, 2014), À60 K/decade at 350 km for daytime hours at Saint Santin/Nancay (Donaldson et al, 2010), À10 to À15 K/decade at F 2 -layer heights for day-time hours at Tromso (Ogawa et al, 2014), and À20 K/decade at 350 km for daytime hours at Millstone Hill (Zhang & Holt, 2013). A recent analysis by Zhang et al (2016) of Sondrestrom and Chatanika/ Poker Flat ISR observations has shown that the high latitude long-term trend results are compared to those from the Millstone Hill mid-latitude dataset.…”
Section: Discussionsupporting
confidence: 86%
“…This gives cooling rate of ∼(3-4) K/decade analyzing a period of 30-40 years. This is close to an exospheric temperature trend of À1 to À2 K/decade estimated from satellite drag observations (Emmert, 2015) and much smaller than Tex trends inferred from ground-based ISR measurements: À18 K/ decade for noontime exospheric temperature at Millstone Hill (Oliver et al, 2014), À60 K/decade at 350 km for daytime hours at Saint Santin/Nancay (Donaldson et al, 2010), À10 to À15 K/decade at F 2 -layer heights for day-time hours at Tromso (Ogawa et al, 2014), and À20 K/decade at 350 km for daytime hours at Millstone Hill (Zhang & Holt, 2013). A recent analysis by Zhang et al (2016) of Sondrestrom and Chatanika/ Poker Flat ISR observations has shown that the high latitude long-term trend results are compared to those from the Millstone Hill mid-latitude dataset.…”
Section: Discussionsupporting
confidence: 86%
“…Doornbos et al (2008) similarly used two-line orbital element sets (TLEs) on ~50 objects to produce low order corrections to empirical models during the year 2000; they found that the global average correction term dominates over the other spherical harmonic terms. Emmert (2009Emmert ( , 2015 combined analyses of TLEs from ~5000 objects to produce a historical reconstruction, back to 1967, of global average density as a function of altitude; this time series is shown, for 400 km altitude, in Fig. 1.…”
Section: Orbit-derived Mass Densitymentioning
confidence: 99%
“…If precision orbit ephemerides are available (for example, for satellites with GPS receivers or satellites with laser ranging observations), it is possible to produce density estimates on time scales of two or more orbits (McLaughlin et al, 2011;Lechtenberg et al, 2013). Storz et al (2005), Doornbos et al (2008), and Emmert (2009Emmert ( , 2015 combined analyses from different objects to produce global specifications of density. These specifications are essentially corrections to empirical thermospheric models for specific epochs.…”
Section: Orbit-derived Mass Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, we prefer here to rely on a simple lowpass filter while being aware that it is open to improvement. We use a dataset of globally-averaged densities computed by Emmert (2009Emmert ( , 2015a. The data cover the period from 1967 to 2011 at heights from 200 to 600 km.…”
Section: Comparison With the Thermospheric Densitymentioning
confidence: 99%